Character Education between The Western Context and Islamic Perpective - Sarwadi Sarwadi; Husna Nashihin (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
Character education is essential in Indonesia. The rising crime rate and other instances of moral failings are warning signs that the bulk of people's character is in a dangerous state. According to the constitution, the goal of national education is to produce people who are noble in character as well as skillful and clever. The character education policy guidelines, which comprise 18 characters that excel, mandate this (religious, honest, disciplined, tolerant, and so on). Character education and Akhlak are comparable concepts from the western context and an Islamic perspective. Islam's principal sources for moral instruction are the Qur'an and Hadith, with the Prophet Muhammad SAW serving as an example. The suggested approach to character education in Islam is based on a mental-spiritual approach through soul management, habituation, an exemplary lifestyle, and a healthy environment that involves three different educational institutions: schools, families, and communities.